Occupational health and safety policy and compliance audit for forklift operator profession in a company with specific production, packaging and distribution of mineral waters - Anișoara Habuc; Claudiu Babiş; Elena Anda Botoc; George Mit; Andrei Dimitescu (Journal of Research and Innovation for Sustainable Society)
The policy in the field of environment, occupational health and safety is embodied in objectives established and communicated at all levels of the organization and for all operations included in the scope of the management system, which are monitored, analyzed and reviewed periodically, so as to ensure: the planning, implementation, maintenance and continuous improvement of the effectiveness of an environmental management system, occupational health and safety oriented towards the satisfaction of all compliance obligations applicable in this field; training, awareness, stimulation and consultation of employees in order to understand the impact of the organization's activities, products and services on the environment, occupational health and safety of their responsibilities in order to actively support management programs and perform work tasks in conditions of environmental protection and occupational safety; to ensure that decisions on occupational health and safety are taken taking into account the need to promote actions to prevent occupational injuries and diseases.